Levantamento fotométrico nas bandas J, H e K de estrelas variáveis na região central de Cygnus OB2 - Julia Maria Torres Roquette (2013)
Cygnus OB2 is an OB association located in the direction of the Local Spiral Arm, harbouring some of the most massive and luminous stars in the Galaxy. Studying its high mass population, we learned that it is a rich star forming region, localized behind a dust cloud which is responsible for the high extinction measured in that area of the sky (10 - 20MV). Its estimated age of 3Myr makes it an appropriate target fot studying young stars. We performed a photometric variability survey in this region using near infrared lters (JHK), with the Wide Field Camera (WFCAM) of the United Kingdom Infrared Telescope (UKIRT), during 112 nights, unevenly spaced in a period of 217 days. A total area of 52'; 96' x 52'; 96 was covered with Cygnus OB2 in its center. The central region of the observed area (1/16 of the total data) was organized as a light curve catalogue. According to light curve characteristics objects with high lter correlationwere selected. Provisional classication was applied according to variability type, using known techniques for discrete time series analysis like Fourier decomposition, graphic cross correlation and deviation between lters, phase dispersion and least square fitting. We present here the implementation and use of such techniques. In case of periodic variability we performed period and amplitude measurements.